IoT application technologies for agriculture in Latin America during the COVID-19 pandemic (LACCEI, 2024)
IoT digitizes any plant of agricultural processes simplifying the activities0 producing products of higher quality in a set period and optimizing automatic irrigation systems. Evaluate IoT application technologies for Latin American agriculture during the COVID-19 pandemic, through systematic search engine database vision0 obtaining 78 publications between 2019 and 2022, considering 14 studies by inclusion criteria of methodological heterogeneity. The main IoT application technologies for smart agriculture: according to the quantitative approach in dimension 10 3 articles contribute to architecture and 1 to irrigation control0 while in dimension 20 2 articles contribute to environmental monitoring and 4 to efficient water management0 the same in qualitative approach in dimension 10 2 articles show trends of the industrial revolution in food, 2 in automation architecture and 2 in the intelligent decision by artificial vision0 also in dimension 20 2 articles studied trends of industrial revolution 4.0 and 4 intelligent precision agriculture and computer vision. Therefore, quantitative studies were based on experimental applications of data architecture design to optimize water consumption according to environmental conditions0 reviewing in qualitative approach trend documents of the Industrial Revolution 4.0 applying artificial vision.